Design and development of wideband antennas for ground penetrating radar - Tan, Edmund Guo Hao (2019)
This final year project report presents a study of wideband antennas for ground penetrating radar. After the introduction and literature review of the antenna fundamental concepts, the subsequent sections of the report focus on the study of several types of antennas, namely the antipodal Vivaldi antenna and tapered-slot antenna. Two different bowtie antennas design that are used in different scenario will also be proposed in the later sections. The study of the bowtie antennas includes theoretical analysis, software design using HFSS, hardware fabrication, and lastly the testing of the antenna using vector network analyzer. The tapered-slot antenna and antipodal Vivaldi antenna are very popular in the recent years due to its ultra-wide band, easy fabrication and impedance matching. However, these two types of antenna have several disadvantages. For instance, the design cost is relatively expensive if the antenna requires several layers, the antenna transmitting signal depth issue and the complexity of the design. Hence, a bowtie antenna is proposed with the intention of performing high bandwidth, simpler structure for the ease of fabrication and lower overhead costs when producing the antenna.